A case of small intestinal metastasis of breast cancer diagnosed by intestinal obstruction - Nishinakagawa, Shuta; Inuyama, Mitsuko; Kaneda, Yoko; Ishii, Saki; Orihara, Shinya; Oba, Nobuyuki; Nakajima, Kazuaki; Ogino, Yu; Shiono, Saori; Ikegami, Ryo; Nohara, Shigeo (Progress of Digestive Endoscopy, 2025)
A female in her 80s underwent mastectomy and axillary dissection (III) for a right invasive lobular carcinoma. Three months later, recurrence was observed in the chest wall and lymph nodes, and the patient underwent resection. Treatment with TS-1 was continued, but it was discontinued after approximately one year, at her request. Two months later, the patient presented to the emergency department with a chief complaint of repeated vomiting. Computed tomography (CT) of the abdomen revealed stenosis from the fourth segment of the duodenum to the proximal jejunum, and upper gastrointestinal endoscopy revealed circumferential wall thickening in the fourth segment of the duodenum. Biopsy results revealed a histological pattern consistent with invasive lobular carcinoma, and the patient underwent laparoscopic gastrojejunal bypass surgery. Intra-operative findings revealed a small intestinal metastasis of invasive lobular carcinoma. The patient was discharged from the hospital within two weeks, but her general condition gradually worsened, including peritoneal dissemination, and she died at home approximately one month post-diagnosis.